2002
DOI: 10.1086/344314
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Analysis of Hepatitis C Virus Transmission between Injection Drug Users

Abstract: Hepatitis C virus (HCV) genotype 1a and 3a partial NS5B gene segment sequences obtained from 154 HCV-infected injection drug users were studied to determine the extent to which HCV transmission occurs between injection drug user communities in London, Edinburgh, Glasgow (United Kingdom), Marseilles (France), and Melbourne. Phylogenetic relationships between sequences were analyzed by conventional methods and by a recently developed method that numerically scores the extent of sequence segregation between group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 27 publications
2
61
1
Order By: Relevance
“…2). The method for scoring is related to that used by the Association Index, a method developed previously to quantify the degree of segregation of different predefined groups (6,47).…”
Section: Resultsmentioning
confidence: 99%
“…2). The method for scoring is related to that used by the Association Index, a method developed previously to quantify the degree of segregation of different predefined groups (6,47).…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of such strains may arise through travel or immigration (Bernier et al, 1996;Morice et al, 2001;Stuyver et al, 1995), by the import and export of contaminated blood products (Kinoshita et al, 1993) or through networks of injecting drug users (Cochrane et al, 2002). It is interesting to note that the two transmission patterns described above have also recently been noted for another virus; in an analysis of HIV-1 subtype B in the UK, Hue et al (2005) found at least six co-circulating transmission clusters within a single risk group.…”
Section: Discussionmentioning
confidence: 98%
“…The second pattern is represented by the individual Chinese isolates of HCV that are more closely related to non-Chinese isolates of HCV, which most likely represent multiple, sporadic migration of strains of HCV. We tried to investigate which countries these sporadic strains were derived from but our phylogenies were insufficiently resolved to answer this question reliably (data not shown).The introduction of such strains may arise through travel or immigration (Bernier et al, 1996;Morice et al, 2001;Stuyver et al, 1995), by the import and export of contaminated blood products (Kinoshita et al, 1993) or through networks of injecting drug users (Cochrane et al, 2002). It is interesting to note that the two transmission patterns described above have also recently been noted for another virus; in an analysis of HIV-1 subtype B in the UK, Hue et al (2005) found at least six co-circulating transmission clusters within a single risk group.…”
mentioning
confidence: 99%
“…A disadvantage of this study type is that transmission inference is based on phylogenetic data derived from strains of long-standing infection combined with information on current injecting partners, similar to the contemporaneous residential data used in the current study. Other investigators have taken phylogenetic clustering outcome as direct evidence of individual membership in a contact network (34)(35)(36)(37)(38).…”
Section: Gt3mentioning
confidence: 99%